2015
DOI: 10.3354/ame01738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sunlight on prokaryotic organic carbon uptake and dynamics of pigments relevant to photoheterotrophy in the Adriatic Sea

Abstract: Marine photoheterotrophic microorganisms are capable of using light to meet their energy requirements and organic compounds as both carbon and energy sources. We still have little knowledge of the extent to which stimulation of these microorganisms by light could affect the estimates of organic carbon uptake. We evaluated the light and dark prokaryotic organic carbon uptake ( 3 H-leucine) rates in a grid of stations covering the whole Adriatic Sea during winter and late summer. Light-exposed (photosyntheticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…In this research, fluorescence, as a proxy of chlorophyll, nitrates, nitrites, phosphates, and total dissolved phosphates, influenced the abundance of AAPs. Besides, the correlation found between bacteria and AAPs, which has also been reported by Celussi et al [11], could be explained by the fact that both AAPs and heterotrophic bacteria rely on labile DOC, part of which is released by phytoplankton. Secondly, AAPs and phytoplankton have a similar dependence on light [90], and this relationship may reflect the same dependence on limiting nutrients, such as phosphorus or nitrogen [15].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In this research, fluorescence, as a proxy of chlorophyll, nitrates, nitrites, phosphates, and total dissolved phosphates, influenced the abundance of AAPs. Besides, the correlation found between bacteria and AAPs, which has also been reported by Celussi et al [11], could be explained by the fact that both AAPs and heterotrophic bacteria rely on labile DOC, part of which is released by phytoplankton. Secondly, AAPs and phytoplankton have a similar dependence on light [90], and this relationship may reflect the same dependence on limiting nutrients, such as phosphorus or nitrogen [15].…”
Section: Discussionsupporting
confidence: 73%
“…Šantić et al [12] investigated AAPs abundances along the eastern Adriatic, in coastal and transitional waters, and found that their proportion in total prokaryotes was 7.3% (±4.3%). Celussi et al [11] pointed out that the concentration of bacteriochlorophyll a, the main pigment of AAPs, could be converted into abundance. Therefore, AAPs might represent up to 10% of total prokaryotes in the open Adriatic Sea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kruskal‐Wallis (K‐W) ANOVA was utilized to detect significant differences in prokaryotic activities among the western Mediterranean, the eastern Mediterranean and the Adriatic Sea. The latter was separated from the eastern Mediterranean due to its high productivity (Fonda Umani, ) and DOC concentration at depth (Celussi et al ., ). The median test post hoc was applied if K‐W showed significant statistics.…”
Section: Methodsmentioning
confidence: 97%
“…The first study of AAPs in the Adriatic Sea referred to their pigment BChl a along a latitudinal transect covering the entire Adriatic Sea. By converting pigment concentration to abundance, the authors assumed that AAPs could represent up to 10% of the total prokaryotes (Celussi et al, 2015). Based on the abundance of cells using infrared epifluorescence microscopy, AAPs were described for the first time on a spatial scale in coastal and estuarine (transitional) waters along the eastern Adriatic coast in summer (Šantić et al, 2017).…”
Section: Spatio-temporal Distribution Of Aerobic Anoxygenic Phototrophsmentioning
confidence: 99%